Lucerne meal in the diet of indigenous chickens: a review - Ginindza, Muzi M. (Frontiers in Animal Science, 2023)
Indigenous chicken production consists of an array of activities important to smallholder poultry farmers in Africa. One of the many factors influencing their production and threating the local food security is in the area of nutrition, particularly, that related to protein supplementation. The available feed resources to farmers are not enough to sustain the productivity of the chickens. Hence, the chickens’ diets often require nutritional supplementation. There is therefore an urgent need for the validation of locally grown feed ingredients to improve the sustainability of poultry production in sub-Saharan Africa. A dietary ingredient that may be used in the diets of chickens is lucerne (Medicago sativa), which is also known as alfalfa. In South Africa, lucerne is the most cultivated forage legume and approximately 1.3 million metric tonnes of lucerne are produced per year. Lucerne has high nutritional value, as it is a source of protein, amino acids, vitamins, and fatty acids. The potential of lucerne as a feed resource for indigenous chickens should, therefore, be investigated so that strategies to improve the nutrition of such chickens can be developed. The purpose of this review was to highlight lucerne as a potential dietary ingredient for indigenous chickens and discuss its effects on the productivity of broilers, egg-layers, and dual-purpose chickens.